2015
DOI: 10.1016/j.physbeh.2015.04.053
|View full text |Cite
|
Sign up to set email alerts
|

Estrogens, androgens and generalized behavioral arousal in gonadectomized female and male C57BL/6 mice

Abstract: General arousal has been operationally defined as enhanced motor activity and enhanced intensity of response to sensory stimuli. Even though the effects of gonadal hormones on mating behavior have been much studied, their potential effect on generalized arousal, as defined above, has never been evaluated. In the present study we employed a thoroughly validated assay of general arousal to determine the effects of estradiol (E) and testosterone (T) in gonadectomized female and male mice, respectively. The steroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Even without any of the experimental treatments, home‐cage locomotor activity, as opposed to open field exploratory locomotor behavior, was much greater in female mice than male mice. Of particular note, another study has shown that this difference in activity still can persist even if female rodents are ovariectomized (Chu, Gagnidze, Pfaff, & Ågmo, ). Although removal of the ovaries does not affect locomotor activity, centrally located (i.e., brain) estrogens and estrogen receptors (ER) may still be implicated in why female mice exhibit more movement than males.…”
Section: Discussionmentioning
confidence: 99%
“…Even without any of the experimental treatments, home‐cage locomotor activity, as opposed to open field exploratory locomotor behavior, was much greater in female mice than male mice. Of particular note, another study has shown that this difference in activity still can persist even if female rodents are ovariectomized (Chu, Gagnidze, Pfaff, & Ågmo, ). Although removal of the ovaries does not affect locomotor activity, centrally located (i.e., brain) estrogens and estrogen receptors (ER) may still be implicated in why female mice exhibit more movement than males.…”
Section: Discussionmentioning
confidence: 99%
“…Pfaff and colleagues have demonstrated a role of gonadal steroids in arousal that suggests steroids, while having modest effects on generalized arousal, have a greater effect on reproductive behaviors/sexual arousal, a component of a general arousal (Chu et al, 2015). In our current model of MA-induced enhancement of proceptive behaviors, MA may prime a specific neural network involved in female sexual behaviors resulting in enhanced activation when EB and P are present.…”
Section: Discussionmentioning
confidence: 99%
“…Both excitatory and inhibitory neurobiological factors influence sexual motivation (reviewed in 10, 30); however, this report will focus on the neurobiological factors that increase motivation for sexual behaviors. One such influence on sexual motivation is non-specific or generalized arousal, which sets the general level of activity in the brain and can influence specific sexual motivations (14, 31). Indeed, this process may explain how sexual arousal increases subjective sexual desire.…”
Section: Models Of Sexual Motivation and Arousalmentioning
confidence: 99%
“…Several classic studies have demonstrated the role of both estradiol and progesterone in triggering both proceptive and receptive sexual behaviors in the rat (87). These hormones strongly affect the responses to sexually relevant stimuli, with modest effects on generalized arousal (31). The neural circuitry for lordosis, particularly the role of the ventrolateral portion of the ventromedial hypothalamus (vlVMN), has been well established (88, 89); however, the neural circuitry underlying sexual motivation in the female has not been as well elucidated.…”
Section: Animal Models Of Sexual Behaviormentioning
confidence: 99%
See 1 more Smart Citation